Experimental Study on the Mechanical, Durability, and Microstructural Properties of Concrete With Partial Cement Replacement With Coffee Husk Ash and Rice Husk Ash - Fikreyesus Demeke Cherkos (Advances in Materials Science and Engineering)
The environmental impact of concrete production, mainly due to cement manufacturing, has prompted the search for sustainable alternatives, such as agricultural byproducts. Rice husk ash (RHA) and coffee husk ash (CHA) show promise as supplementary cementitious materials that can enhance concrete’s strength and durability. However, RHA’s fine particles reduce workability, and CHA’s lower silica content limits its pozzolanic reactivity. While both have individual benefits, their combined effects on concrete properties remain underexplored. This study investigates the influence of RHA and CHA as partial cement replacements on the fresh and hardened properties of concrete. A C-25 mix was designed using the ACI 211.1 method, with RHA and CHA proportions ranging from 0% to 25% and 0% to 15%, respectively, in 5% increments. Workability was assessed using slump tests, and mechanical properties—including compressive, split tensile, and flexural strengths—as well as durability (measured through water absorption, strength, and weight loss under 5% sulfuric acid exposure) were evaluated. The results show that both RHA and CHA significantly affect workability, strength, and durability. RHA reduced workability more than CHA due to its finer particles and higher water absorption. The optimal mix of 10% RHA and 5% CHA improved compressive strength by 5.04% and 7.87% at 28 and 56 days, respectively, and enhanced flextural and split tensile strengths by 11.45% and 7.41%, respectively. Durability tests showed that the combination of 15% RHA and 5% CHA (R15C5) significantly reduced water absorption and improved sulfuric acid resistance, indicating a denser microstructure and greater environmental resilience. SEM analysis shows that adding RHA and CHA enhances concrete’s microstructure. The R10C5 mix (10% RHA and 5% CHA) strikes a good balance of strength and refinement. While R15C5 (15% RHA and 5% CHA) improves durability, it shows similar strength and durability to R10C5 due to dilution and higher water demand, as confirmed by statistical analysis. These findings demonstrate that the synergistic use of RHA and CHA can optimize concrete performance, providing a sustainable alternative for enhancing both strength and durability. However, excessive use of RHA or CHA beyond the optimal proportions can compromise performance due to interference with hydration and workability.